Gamma-Phase Shifting in Awake Monkey Visual Cortex - Vinck, Martin (J Neurosci, 2010)
Gamma-band synchronization is abundant in nervous systems. Typically, the strength or precision of gamma-band synchronization is studied. However, the precise phase with which individual neurons are synchronized to the gamma-band rhythm might have interesting consequences for their impact on further processing and for spike timing-dependent plasticity. Therefore, we investigated whether the spike times of individual neurons shift systematically in the gamma cycle as a function of the neuronal activation strength. We found that stronger neuronal activation leads to spikes earlier in the gamma cycle, i.e., we observed gamma-phase shifting. Gamma-phase shifting occurred on very rapid timescales. It was particularly pronounced for periods in which gamma-band synchronization was relatively weak and for neurons that were only weakly coupled to the gamma rhythm. We suggest that gamma-phase shifting is brought about by an interplay between overall excitation and gamma-rhythmic synaptic input and has interesting consequences for neuronal coding, competition, and plasticity.